Primary membranous glomerulonephritis: the role of serum and urine biomarkers in patient management - Maifata, Sadiq Mu'azu; Hod, Rafidah; Zakaria, Nor Fadhlina; Abd. Ghani, Fauzah (MDPI, 2019)
The detection of phospholipase A2 receptor (PLA2R) and thrombospondin domain containing 7A THSD7A among primary membranous glomerulonephritis (MGN) patients transformed the diagnosis, treatment monitoring, and prognosis. Anti-PLA2R can be detected in 70–90% of primary MGN patients while anti-THSD7A in 2–3% of anti-PLA2R negative primary MGN patients depending on the technique used. Serum and urine samples are less invasive and non-invasive, respectively, and thus can detect the presence of anti-PLA2R and anti-THSD7A with higher sensitivity and specificity, which is significant in patient monitoring and prognosis. It is better than exposing patients to a frequent biopsy, which is an invasive procedure. Different techniques of detection of PLA2R and THSD7A in patients’ urine and sera were reviewed to provide newer and alternative techniques. We proposed the use of biomarkers (PLA2R and THSD7A) in the diagnosis, treatment decision, and follow-up of patients with primary MGN. In addition, other prognostic renal biomarkers like retinol binding protein (RBP) and beta-2 microglobulin were reviewed to detect the progression of renal damage for early intervention.